Redeeming the communist past : the regeneration of communist parties in East Central Europe - Grzymała-Busse, Anna Maria, 1970- (Cambridge studies in comparative politics., 2002)
This major study examines one of the most surprising developments in East Central European politics after the democratic transitions of 1989: the completely unexpected regeneration of the former communist parties. After the collapse of the communist regimes in 1989, these ruling communist parties seemed consigned to oblivion. However, confounding scholarly and popular expectations, all of the parties survived, with some even returning to power.